Augmentation of dye-sensitized solar cell photovoltaic conversion efficiency via incorporation of terpolymer Poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) based gel polymer electrolytes. (3rd May 2021) - Farhana, N.K.; Bashir, Shahid; Ramesh, S.; Ramesh, K.
Abstract: A dye-sensitized solar cell (DSSC) is the alternative photovoltaic technology for the replacement of the standard photovoltaic liquid electrolyte-dependent cell. Gel polymer electrolyte (GPE) was used in this research to replace the volatile liquid electrolyte. This GPE has been developed using terpolymer type Poly(vinyl butyral-co-vinyl alcohol-co-vinyl acetate) P(VB-co-VA-co-VAc), iodine (I2 ), sodium iodide (NaI), and ethanol. The findings from X-ray diffraction (XRD) showed the effect of NaI on the crystalline content of the electrolyte systems. Samples showed higher conductivity with a lower degree of crystallinity. Differential scanning calorimetry (DSC) analysis revealed the slight decrease in melting temperature (Tm ) upon addition of NaI salts. The thermogravimetric analysis (TGA) showed that GPE ′s thermal stability decreases as NaI salt content increases. Fourier-transform infrared (FTIR) results indicated that P(VB-co-VA-co-VAc) interacted with NaI. The highest room temperature ionic conductivity of 3.22 × 10 −3  S cm −1  by the sample with 30 wt % NaI. Temperature-dependent findings showed that all GPE samples adhere to the Arrhenius equation in the temperature range from 303 K to 373K and found the lowest activation energy obtained by the sample with 30 wt % NaI as 0.066 eV. Dielectric and modulus properties of all samples have been studied. DSSC fabricated using the electrolyte containing 30 wt% NaI has achieved the highest conversion efficiency of 4.01% with maximum JSC value of 12.52 mA cm −2, VOC of 0.61 V, and fill factor (FF) of 51.8%. Graphical abstract: Image 1 Highlights: Efficiency enhancement in a DSSC with terpolymer type and NaI salt is reported. Incorporation of NaI improves the properties and performance of P(VB-co-VA-co-VAc) GPEs. Improvement in D app value of I3 − based GPE by the increased NaI content. 30 NaI:70 P(VB-co-VA-co-VAc) (wt.%) mixture produced maximum J SC and 4.01% efficiency.